2011
DOI: 10.3109/09637486.2011.572545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake among adults in Trinidad and Tobago and development of a quantitative food frequency questionnaire to highlight nutritional needs for lifestyle interventions

Abstract: A list of commonly consumed foods in Trinidad and Tobago was obtained and a draft QFFQ was prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…The study obtained higher prevalence of underweight among women of food unsecured household. Similar result was reported by another study in Trinidad [42], where authors found significant association of food insecurity with underweight. Women who had genital discharge in last one year were more undernourished; because, vaginal or genital discharge makes women more suspicious to underweight.…”
Section: Discussionsupporting
confidence: 79%
“…The study obtained higher prevalence of underweight among women of food unsecured household. Similar result was reported by another study in Trinidad [42], where authors found significant association of food insecurity with underweight. Women who had genital discharge in last one year were more undernourished; because, vaginal or genital discharge makes women more suspicious to underweight.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly in China, plant commodities were associated with 48% (930) of foodborne disease outbreaks which occurred from 2003–2008 [ 61 ]. There are currently no published reports identifying the food vehicles for the transmission of foodborne disease in T&T. However, a survey of dietary consumption patterns in T&T revealed that 38% of participants regularly ate mixed raw vegetable salad, and a further 22% reported eating raw lettuce or tomatoes, thus the risk of consumption of contaminated produce is very apparent [ 62 ]. This high consumption rate, coupled with low compliance of farmers to Good Agriculture Practices, makes vegetables an important risk factor for foodborne disease [ 63 ].…”
Section: Knowledge Gaps In Stec and Salmonella mentioning
confidence: 99%
“…However certain broad categories, such as peas, beans, treenuts, those referring to fish and those labelled as 'other', were lacking in detail about the specific foods that made up the category. To code these categories in a way that would more closely reflect the Trinidadian diet we referred to the food list of a QFFQ that was recently developed specifically for this population by one of the authors (S.S.) (17) . Using the 146-item food list as a guide, we coded 'peas' as pigeon peas, 'beans' as green beans, and 'treenuts' as almonds and cashew nuts.…”
Section: Methodsmentioning
confidence: 99%
“…Another important limitation is the lack of detail regarding the precise make-up of certain commodity groupings, such as types of fish, fruits and vegetables. To try to overcome this issue we populated these categories using information about commonly consumed foods from a QFFQ developed specifically for a Trinidadian population (17) . Although this could give only an approximation of true supply for these categories, it ensured that foods typically consumed in Trinidad and Tobago but which were not already specifically accounted for in the food balance sheets would be represented.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation